2015
DOI: 10.1111/sms.12639
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences of muscle and crural fascia origins in relation to the occurrence of medial tibial stress syndrome

Abstract: Although women reportedly have a higher prevalence of medial tibial stress syndrome (MTSS) than men, the possible role of gender-based anatomical differences has not been investigated. The aim of the present study was to investigate the presence of gender-based differences in the range of muscle attachments along the entire medial tibia, the proportion of muscle attachment at the middle and distal thirds of the medial margin of the tibia, the structure of the crural fascia, and chiasm position. The specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 18 publications
1
26
0
4
Order By: Relevance
“…However, several factors other than mechanical loading may cause sex‐related differences. Many studies reported that there were differences in the morphology of the foot based on sex, including arch rigidity (Zifchock, Davis, Hilstrom, & Song, ), intersegmental motion (Lee, Seo, Kim, Kim, Lee, & Choi, ; Takabayashi et al, ), origin of the muscles (Edama et al, ), foot shape (Lee, Kouchi, Mochimaru, & Wang, ; Tomassoni, Traini, & Amenta, ; Seghazadeh, Kitano, & Okura, 2015; Smith, ; Wunderlich & Cavanagh, ), and the plantar loading pattern (Chiu, Wu, & Chang, ; Putti, Arnold, & Abboud, ,b; Queen, Vap, Moorman, Carrett, & Butler, ; Sims, Hardaker, & Queen, ). Furthermore, sexual hormones affect the sex‐based differences in bone robustness (Haapasalo, Sievanen, Kannus, Heinonen, & Oja, 1996; Järvinen et al, ; Kannus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several factors other than mechanical loading may cause sex‐related differences. Many studies reported that there were differences in the morphology of the foot based on sex, including arch rigidity (Zifchock, Davis, Hilstrom, & Song, ), intersegmental motion (Lee, Seo, Kim, Kim, Lee, & Choi, ; Takabayashi et al, ), origin of the muscles (Edama et al, ), foot shape (Lee, Kouchi, Mochimaru, & Wang, ; Tomassoni, Traini, & Amenta, ; Seghazadeh, Kitano, & Okura, 2015; Smith, ; Wunderlich & Cavanagh, ), and the plantar loading pattern (Chiu, Wu, & Chang, ; Putti, Arnold, & Abboud, ,b; Queen, Vap, Moorman, Carrett, & Butler, ; Sims, Hardaker, & Queen, ). Furthermore, sexual hormones affect the sex‐based differences in bone robustness (Haapasalo, Sievanen, Kannus, Heinonen, & Oja, 1996; Järvinen et al, ; Kannus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, subjects with MTSS exhibited greater hindfoot and forefoot eversion and abduction during walking and running than subjects without MTSS. The tibialis posterior originates from the posterior of the tibia and fibula and attaches to the navicular, cuneiform, and second through the fourth metatarsal base . The flexor digitorum longus and soleus originate from the posteromedial border of the tibia, and attach to the distal phalanges of the foot and medial calcaneal tuberosity, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…The tibialis posterior originates from the posterior of the tibia and fibula and attaches to the navicular, cuneiform, and second through the fourth metatarsal base . The flexor digitorum longus and soleus originate from the posteromedial border of the tibia, and attach to the distal phalanges of the foot and medial calcaneal tuberosity, respectively . The soleus is an invertor of the calcaneus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at anatomical differences between men and women, Edama and colleagues () showed gender‐based differences in the attachment and position of the muscle and fascia on the tibia. This most likely explains some of the reason for the higher incidence of medial tibial stress syndrome in women athletes compared with men.…”
Section: Discussionmentioning
confidence: 99%